Sporadic multicentric lymphoma in a Nelore calf - Bezerra, Alexandre O.; Lima, Stephanie C.; Araújo, Marcelo A.; Oliveira, Valdemir A.; Ávila, Larissa G.; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2015)
A case of sporadic multicentric lymphoma in a Nelore calf is reported. Anatomic presentation, age of affected animal, and cytology done on fine needle aspiration biopsy from lymph node supported a presumptive clinical diagnosis. At necropsy there were multiple cream or white soft to firm masses of varying sizes, affecting lymph nodes, kidneys, myocardium, liver, retrobulbar tissues, lymph nodes, bone marrow, spleen, and dura mater; with a mitotic index of 90%. A tentative classification of the neoplasm as lymphoblastic lymphoma was made based on immunohistochemistry.